Whose `Special Treatment'? Heterosexism and the Problems with Liberalism - Brickell, Chris (Sexualities, 2001)
This article examines the circulation of heterosexist positions within several recent New Zealand media texts. It argues that a recent form of discourse engages liberal language and assumptions in ways that support the privileged position of heterosexuality and the marginalization of homosexuality. The examples given highlight not only the tenor of some recent representations of homosexuality, but also some problems within liberalism. Most notable of these are liberalism's individualism and its failure to recognize the systemic nature of hierarchical power relationships and the constituting of lesbian and gay subjectivities within these relationships. These problems allow liberalism to play an active part in processes of domination and subordination.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; capitalisme; cours; discipline; discours médiatique; histoire; hétérosexisme; libéralisme; nouvelle-zélande; océanie; premier cycle; périodes historiques; rapports de domination; régions géographiques; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; violences

Les pratiques traditionnelles affectant la santé physique et mentale des femmes; l'excision et l'infibulation - situation actuelle et perspectives d'avenir - Vissandjée, B.; Ndejuru, R.; Kantiébo, M.; Renaud, J.; Aïthachimi, L.; Levine, L.; Lapointe, M. (Institut universitaire SHERPA, 2001)
L’excision et l’infibulation sont parties intégrantes des traditions de nombreuses sociétés africaines issues majoritairement de la région subsaharienne. En contexte canadien, aucune information statistique n’est présentement disponible sur la prédominance de cette pratique, malgré le fait que de nombreux intervenants soupçonnent que plusieurs immigrant(e)s en provenance de ces pays sont susceptibles de faire subir ces pratiques à leurs fillettes. Cette étude qualitative explore les valeurs et les croyances des immigrant(e)s par rapport à ces pratiques traditionnelles, tout en cernant les défis de leur processus d’intégration au Canada et leur recours aux services de santé.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; care; corps; cours; discipline; interculturalité; migration; médecine; point de vue situé; premier cycle; périodes historiques; québec; régions géographiques; sciences; sciences humaines; sciences infirmières; sex2283; sexologie; sexualité; thématiques; violences